Human lung ex vivo infection models - Hocke, Andreas C. (Cell Tissue Res, 2016)
Pneumonia is counted among the leading causes of death worldwide. Viruses, bacteria and pathogen-related molecules interact with cells present in the human alveolus by numerous, yet poorly understood ways. Traditional cell culture models little reflect the cellular composition, matrix complexity and three-dimensional architecture of the human lung. Integrative animal models suffer from species differences, which are of particular importance for the investigation of zoonotic lung diseases. The use of cultured ex vivo infected human lung tissue may overcome some of these limitations and complement traditional models. The present review gives an overview of common bacterial lung infections, such as pneumococcal infection and of widely neglected pathogens modeled in ex vivo infected lung tissue. The role of ex vivo infected lung tissue for the investigation of emerging viral zoonosis including influenza A virus and Middle East respiratory syndrome coronavirus is discussed. Finally, further directions for the elaboration of such models are revealed. Overall, the introduced models represent meaningful and robust methods to investigate principles of pathogen-host interaction in original human lung tissue.